Multimodal and Gamified Pedagogical Practice for Awareness of the Child Cancer Topic - Munari, Fernanda; Santos, Paulo Ricardo; Barbosa, Débora; Bassani, Patrícia (Cadernos de Educação Tecnologia e Sociedade, 2022)
Digital technologies are increasingly present in the educational scenario, as their meaning goes far beyond than just being pedagogical resources, as they are constituted by elements from the culture. This study is linked to the institutional research project "Games and Health - Development of a multimodal digital game for training in prevention and care for cancer in children and adolescents". The game is aimed at teachers and health professionals, with the goal of sharing information about the symptoms and early diagnosis of childhood cancer. This study proposes the development of a multimodal and gamified pedagogical practice, articulated with the Educa+Saúde digital game, validating the artifact in a teacher training workshop. The goal is to understand how the proposed intervention model can contribute to raising awareness about the topic in a pedagogical training workshop with pedagogy students. Therefore, the research has an applied nature, with a qualitative approach, based on the Design Science Research methodology (DSR). In this research, it was concluded that the multimodal and gamified pedagogical practice proved to be effective to teach and to raise awareness among the participants of the proposal about the subject of childhood cancer, contributing to the validation of the game and the resource proposed in this study.